Traffic Pollution & Urban Design, Alternatives for Developing Healthy Historical Centers: The Case of Macao - Pinheiro, Francisco Vizeu (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

The role of spirituality and religion in counseling and pyschotherapy of christian clients - Tse, Chau Hung (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The relevance of philosophy, spirituality and religion in counselling & psychotherapy within Asia - kazmi, Sayed Shajaat Hussain (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Study of everyday moral reasoning of senior secondary students in Macao - Ng, Sio Lin (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Strategies to reduce greenhouse gas in Macau: assessment on the potentials of natural gas development - Lei, Chon Kio (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Senior secondary students perceptions of virtue and values: a case study in education in Macau - The Reh, Lawrence (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Korean memorial service for the dead: a re-evaluation of the Christians' understanding - Song, Jeongmin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Adoption of Best Practices for Municipal Solid Waste Recycling Management in Macao - Li, Man Ho (University of Saint Joseph, 2017)
Municipal Solid Waste (MSW) is associated with industrialization, urbanization, and a modern economic development, covering several origins such as households and similar waste streams from commerce and trade. Inappropriate waste management impacts human health and the environment negatively, but also the economy and society in general. Waste is today also seen more and more as resource itself. The world trend is to move from mere waste management to a consistent form of resource management within a circular economy, e.g. in form of an Integrated Waste Management System (IMWS). Concerning Macao, MSW is being transported to the Macao Refuse Incineration Plant for thermal treatment with energy recovery. For 2014 and 2015, the amount of waste transferred to the Macao Refuse Incineration Plant for treatment shows a strong yearly increase (11.3 %) being expected to reach or even exceed the maximum allowable waste handling capacity in near future. Alternative methods for waste treatment and valorization are necessary for an effective and sustainable waste management system in Macao. In this research, three case-studies were carried out to analysis real case scenarios that are considered examples of well-functioning MSW management. They were: 1) LIPOR (Portugal); 2) Resinorte (Portugal) and 3) Hong Kong. A questionnaire was prepared and distributed to Macao residents in order to understand their perceptions and views on the existing solid waste recycling in Macao. According to the results of the case-studies and questionnaire, based on the “Polluter Pays Principle” and “Producer Responsibility Scheme”, the main objective of this research is to suggest best practices for waste recycling and management in Macao for the Government, Company, Recycling Trade Participator and the Individual Level
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Abfaelle sind kostbar!" Konsumethische Perspektiven in Papst Franziskus' Enzyklika Laudaut Si - Gassner, Franz (Eine Wirtschaft, die Leben fördert wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)